PROBABILITY DISTRIBUTION FUNCTIONS APPLIED IN THE WATER REQUIREMENT ESTIMATES IN IRRIGATION PROJECTS - Fernandes, Rafael Dreux Miranda (2019)
Spain contains a third the entire irrigated area of Europe, accounting for 15% of the cultivated area of the country and almost 60% of the national agricultural production. Knowledge of the spatial and temporal variability of reference evapotranspiration (ETo) and the probabilistic theory of extreme events is crucial for the elaboration of sustainable irrigation projects. The objective of this work was to define the frequency distribution that best describes ETo for the design of irrigation systems in the region of Andalusia. We used ETo data for the period 2001 to 2015 from 56 meteorological stations. The values were accumulated over three consecutive days. For all accumulated periods, nine probability distributions were adjusted. The probability distribution that best described ETo for the design of irrigation systems in the region was the Gumbel II distribution. The maximum daily ETo to be considered in irrigation projects in this region is, on average, 10 mm. The accumulated ETo for periods of 5, 10, and 30 days that should be considered are, on average, 42 mm, 78, mm and 224 mm, respectively.